2021
DOI: 10.1177/0363546520987823
|View full text |Cite|
|
Sign up to set email alerts
|

Immobilization in External Rotation and Abduction Versus Arthroscopic Stabilization After First-Time Anterior Shoulder Dislocation: A Multicenter Randomized Controlled Trial

Abstract: Background: Treatment of first-time shoulder dislocation (FSD) is a topic of debate. After high rates of recurrent instability after nonoperative management were reported in the literature, primary repair of FSD significantly increased. At the same time, new concepts were proposed that had promising results for immobilization in external rotation (ER) and abduction (ABD). Purpose: The aim of this study was to evaluate the recurrence rates (primary outcome) and clinical outcomes (secondary outcome parameters) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 50 publications
0
64
0
Order By: Relevance
“…14 However, the results regarding its ability to prevent recurrences in the long term are more controversial, and there is enormous variability in the percentage of recurrences reported depending on the follow-up time in the studies evaluated. 17,18,23,31 Recently, 2 randomized controlled trials published in 2021 reported 2% and 10% recurrence rates after arthroscopic Bankart repair at 24 months of follow-up. 17,23 Moreover, a recent systematic review reported a 6.5% recurrence rate after 3 years of follow-up with arthroscopic Bankart repair.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, the results regarding its ability to prevent recurrences in the long term are more controversial, and there is enormous variability in the percentage of recurrences reported depending on the follow-up time in the studies evaluated. 17,18,23,31 Recently, 2 randomized controlled trials published in 2021 reported 2% and 10% recurrence rates after arthroscopic Bankart repair at 24 months of follow-up. 17,23 Moreover, a recent systematic review reported a 6.5% recurrence rate after 3 years of follow-up with arthroscopic Bankart repair.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the method of repositioning, with Kocher's method recommended, foot stirrups not recommended, and brachial plexus anaesthesia or intraarticular local anaesthesia for repositioning in elderly patients with osteoporosis. There is also no agreement on the type of braking and there is still discussion on whether to immobilise the shoulder joint in internal or external rotation [9][10][11]. A study has reported no difference between these two types of braking in terms of recurrence rates and healing outcomes of joint dislocation and return to activity levels [12].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the method of repositioning, with Kocher's method recommended, foot stirrups not recommended, and brachial plexus anaesthesia or intra-articular local anaesthesia for repositioning in elderly patients with osteoporosis. There is also no agreement on the type of braking and there is still discussion on whether to immobilise the shoulder joint in internal or external rotation (9)(10)(11). A study has reported no difference between these two types of braking in terms of recurrence rates and healing outcomes of joint dislocation and return to activity levels (12).…”
Section: Discussionmentioning
confidence: 99%